Second harmonic reduction method for ZVS operation in a fuel cell system - Kwon, Yong Dae; Park, Jin Hyuk; Lee, Kyo Beum (Journal of Power Electronics, 2020)
This study proposes a second harmonic reduction method for the zero-voltage switching (ZVS) operation of a DC/DC converter in a fuel cell system. In this system, a boost-type DC/DC converter and single-phase inverter are interconnected. Second harmonic oscillations are generated in the DC link that interconnects the DC/DC converter and inverter. The ripple component reduces the input current generated during the ZVS operation. Consequently, the total efficiency of the system is decreased. Stress-induced effects are also experienced by the fuel cell owing to this ripple component, thereby decreasing the life span of the fuel cell. To ameliorate the effects of the second harmonic ripples, a type-II current controller is used in the DC/DC converter to generate an adequate controller gained at the target frequency. The validity of the proposed control method is verified using PSIM simulations and experiments with the use of a fuel cell system rated at 1 kW.
Keywords: Fast dynamic response; Fuel cell system; Second harmonics; Type II; ZVS operation; DC/DC converter; Fast dynamic response controller; Fuel cell system; Second harmonic reduction; Type-II controller; ZVS operation